Risk factors for the appearance of minimal pathologic lesions on vocal folds in vocal professionals - Stojanović Jasmina; Ilić Nevenka; Stanković Predrag; Arsenijević Snežana; Erdevički Ljiljana; Belić Branislav; Živić Ljubica; Banković Dragić (Vojnosanitetski Pregled)
Background/Aim. An excessive use or misuse of voice by vocal professionals may result in symptoms such are husky voice, hoarse voice, total loss of voice, or even organic changes taking place on vocal folds - minimal pathological lesions - MAPLs. The purpose of this study was to identify the type of MAPLs which affects vocal professionals, as well as to identify the risk factors that bring about these changes. Methods. There were 94 vocal professionals who were examined altogether, out of whom 46 were affected by MAPLs, whereas 48 of them were diagnosed with no MAPLs, so that they served as the control group. All these patients were clinically examined (anamnesis, clinical examination, bacteoriological examination of nose and pharynx, radiography of paranasal cavities, allergological processing, phoniatric examination, endo-video-stroboscopic examination, as well as gastroenterologic examination, and finally endocrinological and pulmological analyses). Results. The changes that occurred most often were identified as nodules (50%; n = 23/46) and polyps (24%; n = 11/46). Risk factors causing MAPLs in vocal professionals were as follows: age, which reduced the risk by 23.9% [OR 0.861 (0.786-0.942)] whereas the years of career increase the risk [OR 1.114 (1.000-1.241)], as well as the presence of a chronic respiratory disease [OR 7.310 (1.712- 31.218)], and the presence of gastro-oesophageal reflux disease [OR 4.542 (1.263-16.334)]. The following factors did not contribute to development of MAPLs in vocal professionals: sex, a place of residence, irritation, smoking, endocrinologic disease and the presence of poly-sinusitis. Conclusion. It is necessary to introduce comprehensive procedures for prevention of MAPLs, particularly in high-risk groups. Identification of the risk factors for MAPLs and prevention of their influence on vocal professionals (given that their income depends on their vocal ability) is of the highest importance.